Synthesis methods of 1,2,3-/1,2,4-triazoles: A review - Dai, Jinlian; Tian, Sen; Yang, Xueqing; Liu, Zongliang (Frontiers in Chemistry, 2022)
Triazole, comprising three nitrogen atoms and two carbon atoms, is divided into two isomers 1,2,3-triazole and 1,2,4-triazole. Compounds containing a triazole are one of the significant heterocycles that exhibit broad biological activities, such as antimicrobial, analgesic, anti-inflammatory, anticonvulsant, antineoplastic, antimalarial, antiviral, antiproliferative, and anticancer activities. A great quantity of drugs with a triazole structure has been developed and proved, for example, ketoconazole and fluconazole. Given the importance of the triazole scaffold, its synthesis has attracted much attention. This review summarizes the synthetic methods of triazole compounds from various nitrogen sources in the past 20 years.